Segunyeng Sebagai Sarana Komunikasi Lintas Budaya Dalam Perspektif Kisah Para Rasul 4: 32-37 - Harming; Krismadayanti (Sekolah Tinggi Theologia Ebenhaezer Tanjung Enim, 2023)
The purpose of writing this article is to analyze sequnyeng as a form of cross-cultural communication from the perspective of Acts 4:32-37. The writing method used is a qualitative method with a literature study approach to find data about the culture of the Oma Lung Dayak tribe. Methods The hermeneutic approach is used to investigate, study and discuss the text of Acts 4:32-37 carefully with the aim of finding the meaning contained in the text. The conclusion of